Policy reforms and agriculture development in Central Asia - Babu, Suresh Chandra; Djalalov, Sandjar (Springer, 2006)
The Central Asian republics – Kazakhstan, the Krygyz Republic, Tajikistan, Turkmenistan, and Uzbekistan – are transitioning from centrally planned economies to market-oriented systems. This volume addresses the process and policy reforms these countries face and how the reforms may impact agricultural development in a region that has experienced varying degrees of economic growth over the fifteen years since independence. It offers expert policy research and analysis and provides research-based information for generating policy recommendations that are relevant to each country as well as similar evidence from other transitional economies, including China, Vietnam, and selected Eastern European countries.